Financial stability: the significance and distinctiveness of Islamic banking in Malaysia - Ewa Karwowski (Levy Economics Institute of Bard College, 2009)
This paper explores the significance of Islamic banking in Malaysia for stability in the country's economy as a whole. Neither conventional theory nor Islamic economics puts forward a systematic explanation of financial intermediation; consequently, neither is capable of identifying destabilizing elements in the system. Instead, a flow- of-funds approach similar to Minsky's own is applied to the (post-) modern consumption-led) business cycle and financial (and asset) market. Malaysia's structural current account surplus contributes to the overcapitalization of domestic firms. This in turn finances a financial (as opposed to an industrial), consumptionled (instead of investment-led) business cycle, where banking favors destabilizing asset price inflation. Islamic banks operating interdependently with conventional ones contribute to economic destabilization channeling surplus funds from the corporate to the household sector.
Keywords: E44; E32; P5; Z12; 330; Credit; Islamic banking; financial stability; Islamische Bank; Kreditgeschäft; Finanzmarkt; Malaysia